Morphological characteristics of selected body parts of trigger fishes (Tetradontiformes, Balistidae) from India with details on ultrastructural features of body scales - Sahayak, Satish; Joshi, K. K.; Sanil, N. K. (Indian Journal of Fisheries, 2013)
The morphological characters like shape of teeth, nasal apertures, gill rakers and scales of trigger fishes collected from southern India were studied during the period 2000-2002. Based on the shape of the first and second teeth of the upper and lower jaw, five types have been identified. The anterior nasal aperture has different shapes, which is species specific but the posterior aperture is similar in all species. Based on the shape of the anterior nasal aperture, five types have been identified. The outermost branchial arch possesses gill rakers and based on shape they are divided into five types. Scales on body and caudal peduncle are diamond shaped, whereas scales on cheek are rhomboid, rectangular, square or triangular occurring in different combinations. The arrangement of scales on body, abdomen and caudal peduncle were similar in all the species studied while scales are arranged in three patterns on cheek. Scales on cheek are of seven types based on shape of the scale and type of protuberances it possessed on the posterior margin. Body scales are of five types and scales on abdomen are of three types. Transverse section of body scales under the scanning electron microscope (SEM) revealed that the scales consist of four layers. Studies on the ultrastructure of the anterior margin of the body scales revealed that there are five types; based on the type of protuberances it possesses and there are of four types of posterior margin.